Human rabies deaths in Africa: breaking the cycle of indifference - (:unkn) unknown (My University, 2015)
The current outbreak of Ebola virus disease has mobilized the international community against this deadly disease. However, rabies, another deadly disease, is greatly affecting the African continent, with an estimated 25 000 deaths every year. And yet, the disease can be prevented by a vaccine, if necessary with immunoglobulin, even when administered after exposure to the rabies virus. Rabies victims die because of neglect and ignorance, because they are not aware of these life-saving biologicals, or because they cannot access them or do not have the money to pay for them. Breaking the cycle of indifference of rabies deaths in humans in Africa should be a priority of governments, international organizations and all stakeholders involved.
Keywords: African Research